2016
DOI: 10.1088/0963-0252/25/5/055013
|View full text |Cite
|
Sign up to set email alerts
|

Near-field plume properties of an ion beam formed by alternating extraction and acceleration of oppositely charged ions

Abstract: This paper is devoted to study the expansion of a beam composed of packets of positively and negatively charged ions generated by alternating extraction and acceleration. This beam is extracted from an ion-ion plasma, i.e. the electron density is negligible compared to the negative ion density. The alternating acceleration of ions is ensured by two grids placed in the ion-ion plasma region. The screen grid in contact with the plasma is biased with a square voltage waveform while the acceleration grid is ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 27 publications
5
30
0
Order By: Relevance
“…In contrast, the alternate extraction, subject of our interest in this work, relies on one ion source that extracts and accelerates alternatively positive and negative ions [17]. To insure the overlap of the extracted oppositely charged ion packets and avoid beam stagnation, it has been demonstrated that the frequency of oppositely charged ion packets extraction should be in the low MHz range, typically 1.25 MHz [18]. Indeed, the collisionless expansion of alternatively extracted ion-ion beam in vacuum has been studied numerically via particle-incell (PIC) [18] and fluid [19] simulations.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the alternate extraction, subject of our interest in this work, relies on one ion source that extracts and accelerates alternatively positive and negative ions [17]. To insure the overlap of the extracted oppositely charged ion packets and avoid beam stagnation, it has been demonstrated that the frequency of oppositely charged ion packets extraction should be in the low MHz range, typically 1.25 MHz [18]. Indeed, the collisionless expansion of alternatively extracted ion-ion beam in vacuum has been studied numerically via particle-incell (PIC) [18] and fluid [19] simulations.…”
Section: Introductionmentioning
confidence: 99%
“…To insure the overlap of the extracted oppositely charged ion packets and avoid beam stagnation, it has been demonstrated that the frequency of oppositely charged ion packets extraction should be in the low MHz range, typically 1.25 MHz [18]. Indeed, the collisionless expansion of alternatively extracted ion-ion beam in vacuum has been studied numerically via particle-incell (PIC) [18] and fluid [19] simulations. These works [18,19] show that, a few ion packets away from grid system, the generated ion beam is neutralized and has a free expansion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations